The effect of digital leadership on innovative work behavior: The mediating role of cultural moral and work engagement - Heru Nugroho; Adi Saputro; Dadet Sugiharto (Jurnal Fokus Manajemen Bisnis, 2025)
Digital leadership is considered as the appropriate leadership to face the current rapid and dynamic environmental changes. This study is focused on investigating how moral culture and employee engagement, as well as digital leadership impact innovative work behavior. The sample of this study was 205 respondents from construction Company X. The analysis was using path analysis technique conducted using the SEM-PLS method. The analysis's findings show that digital leadership influences organizational culture  in a beneficial way.  Innovative work behavior is influenced by work engagement, organization culture, and work engagement influences innovative work behavior. However, digital leadership does not directly have a significant effect on innovative work behavior. For construction company management, increasing innovative work behavior can be done by increasing the implementation of digital leadership so that company employees can form a good organizational culture and strong work engagement.